2017
DOI: 10.5194/isprs-archives-xlii-5-w1-227-2017
|View full text |Cite
|
Sign up to set email alerts
|

The 4dilan Project (4th Dimension in Landscape and Artifacts Analyses)

Abstract: ABSTRACT:The project is part of the wider application and subsequent spread of innovative digital technologies involving robotic systems. Modern society needs knowledge and investigation of the environment and of the related built landscape; therefore it increasingly requires new types of information. The goal can be achieved through the innovative integration of methods to set new analysis strategies for the knowledge of the built heritage and cultural landscape. The experimental cooperation between different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Moreover, the false-colour radargrams could be overlapped and visualized on the 2D textured vertical sections of the building, enabling a more intuitive and effective spatial correlation among the results. This correlation is also a result of the work by Chiabrando et al [143], where GPR was used to detect the presence of underground structures around a masonry tower in North-West Italy through superimposition of radar profiles and horizontal orthoimages. Similarly, within a comprehensive investigation of a basilica in North-East Italy [144], the integrated visualization and analysis of GPR and Digital Elevation Models (DEMs) relating to the mosaics led to hypothesizing about the presence of buried structures belonging to the oldest construction phases under the investigated floors.…”
Section: Multisensory Data Collectionsupporting
confidence: 53%
See 1 more Smart Citation
“…Moreover, the false-colour radargrams could be overlapped and visualized on the 2D textured vertical sections of the building, enabling a more intuitive and effective spatial correlation among the results. This correlation is also a result of the work by Chiabrando et al [143], where GPR was used to detect the presence of underground structures around a masonry tower in North-West Italy through superimposition of radar profiles and horizontal orthoimages. Similarly, within a comprehensive investigation of a basilica in North-East Italy [144], the integrated visualization and analysis of GPR and Digital Elevation Models (DEMs) relating to the mosaics led to hypothesizing about the presence of buried structures belonging to the oldest construction phases under the investigated floors.…”
Section: Multisensory Data Collectionsupporting
confidence: 53%
“…In the case of multispectral imaging, as presented in Section 3.3.1, a direct comparison is enabled between CRP surface colorimetric/metric data and TIR, NIR and/or UV surface data, which might be useful to assess the position and quantitative extent of non-visible anomalies, such as material inhomogeneity [129,130,134], energy losses [131], cracks and mechanical damage [132,136], moist areas [133,135] and weathering patterns [53,60]. Differently, in the case of multisensory data collection, as reported in Section 3.3.2, an indirect comparison is enabled between CRP surface colorimetric/metric data and measurements of constructional discontinuities and pathologies across the components; this comparison is detected as variations in radar reflection from underground structures [143][144][145]147,148]; moist areas [142,146]; or variations in ultrasonic velocities in walls [148,150,151], columns [92,152,153] and pillars [154]. In a few applications, the employment of CRP models to accurately set up onsite tests and equipment is also documented [155][156][157].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning "4D Spatial Data Management", it has been identified that it is being used at the urban scale through 3D models of heritage buildings integrated into a GIS platform, with the aim of analyzing the historical evolution and structural changes that have occurred over time in buildings located in the old towns of historic cities [57,59,60].…”
Section: Discussionmentioning
confidence: 99%
“…We cannot make direct comparisons with the 2015 flights, since at the time the images were acquired with a fixed wing drone at a higher altitude. We can compare the results with other experiences (Chiabrando et al 2017c) and how we can see even in the next sections, the use of the total station allows to improve the accuracy of the final results. …”
Section: Survey Planningmentioning
confidence: 97%
“…The common strategy to these tests consisted in generating a Lidar cloud that could have the function of controlling the general accuracy of DSMs derived from low-level flights. The wellestablished workflow, which has provided the best results also on other occasions (Chiabrando et al 2017c) was to record Lidar scans initially by shape (cloud-to-cloud), using ICP (Iterative Closest Points) algorithms for the first registration, and then measure the control points on the complete scan for georeferencing and evaluating the accuracy. In addition, the targets for the registration of the Lidar clouds were obviously surveyed by total station and the processing has been performed using Faro Scene software.…”
Section: Two Different Flight Plannings In (A) and (B) Areasmentioning
confidence: 99%